Evaluation of macroseismic intensities in Mexico from recent earthquakes using ¿Sintió un sismo? (Did you feel it?) - Montalvo Arrieta, Juan Carlos; Sosa Ramírez, Rocío L.; Pérez Campos, Xyoli (UNAM. Instituto de Geofísica, 2017)
Macroseismic investigations with data collected through online surveys has acquired relevance in recent years. Its easy access and low cost allow assessments of the severity of an earthquake from its effects as observed by the population. Furthermore, it is possible to generate attenuation curves for a particular region, visualize the condition of the buildings from a zip code-averaged distribution map, and estimate possible site effects. In regions without a good coverage of seismic networks, macroseismic intensities have proved to be a substitute for instrumental data. In this paper intensity maps for four earthquakes in different regions of Mexico are presented, based on data from the database of ¿Sintió un sismo? program, an online survey implemented in 2014. Less attenuation was found in areas considered tectonically stable than in those considered as active regions.